PWE-180 The Acidic Polysaccharide Component of Soluble Plantain Fibre Inhibits the Adhesion of Diarrhoea-Associated Pathogens Salmonella, Clostridium Difficile and Enterotoxigenic Escherichia Coli to Intestinal Epithelial Cells. (4th June 2013) - Simpson, H L; Parsons, B N; Rhodes, J M; Campbell, B J
Abstract : Introduction: Pathogen-related diarrhoea is a major problem worldwide, causing significant morbidity and mortality each year. Our recent studies have shown that soluble dietary fibre (non-starch polysaccharides, NSP), particularly those from plantain bananas ( Musa spp.), can inhibit the adherence of diarrhoeal pathogens such as Salmonella, Clostridium difficile and enterotoxigenic Escherichia coli (ETEC) to the intestinal epithelium (J. Nutri. Biochem. 24:97–103). Our aim in this study was to elucidate specific polysaccharide components present in soluble plantain fibre that confer bioactivity to block diarrhoeal pathogen interaction with the gut epithelium. Methods: Plantain NSP was separated into neutral and acidic component polysaccharides using Q-Sepharose strong anion-exchange chromatography. Unbound neutral oligosaccharides were collected from the flow-through and Q-Sepharose bound acidic polysaccharide fractions were eluted stepwise with 0.25, 0.5 and 1M NaCl. All fractions were desalted on PD MidiTrap G10 mini-columns. Purified fractions were assessed for inhibitory action on C. difficile 027A, ETEC C410 and S. Typhimurium adherence to human and porcine epithelial cell monolayers in the presence of plantain NSP and its fractions (30 min pre-treatment prior to infection), at MOI 100 for 90 min (for ETEC and Salmonella) or 120 min (for C. difficile ). Adherent colony forming units (CFU) were enumerated by overnight growth on LB-agar. Results: As observed for plantain NSP, at 5mg/mL, a Q-Sepharose-purified acidic polysaccharide fraction of soluble plantain NSP also significantly blocked adhesion to human Caco2 colonocytes of gut pathogens C. difficile, by 52.3±7.3%; ETEC, by 74.8±15.1; and S . Typhimurium, by 92.1±2.91% (all P < 0.001 Kruskal-Wallis; N = 2 experiments, each with n = 3 replicates). Conversely, pre-treatment of Caco2 cells with the neutral polysaccharide fraction of plantain NSP showed little ability to reduce adhesion of C. difficile (10.2% inhibition) and a reduced ability to inhibit interaction of Salmonella or ETEC (46.6% and 39.1% inhibition respectively). Similalrly, acidic fractions of plantain NSP at 5mg/mL also blocked adhesion of S. Typhimurium to porcine enterocytic cell-line B10XI compared to untreated control (N = 4, n = 4; P < 0.01 Kruskal-Wallis). Conclusion: Our findings indicate that the inhibitory activity of plantain NSP against diarrhoeal pathogen interaction with the host intestinal epithelium lies in its acidic (pectic) polysaccharide component. Disruption of bacterial-epithelial adherence to the intestinal mucosa by soluble plant fibres, acting as 'contrabiotics', may prove to be of therapeutic benefit. Disclosure of Interest: H. Simpson: None Declared, B. Parsons: None Declared, J. Rhodes Grant/Research Support from: Provexis plc (UK), Consultant for: A member of advisory boards for Atlantic, Proctor and Gamble, Falk, Conflict with: Lecture fees received from Abbott, Falk, Ferring, Glaxo Smith Kline, Proctor and Gamble, Schering Plough, Shire, Wyeth. With the University of Liverpool and Provexis UK, holds a patent for use of soluble plantain fibre as maintenance therapy for Crohn's disease plus a patent pending for its use in antibiotic associated diarrhoea, B. Campbell Grant/Research Support from: Provexis plc. and Shire, Consultant for: Amgen Inc.